EFFECTIVE RISK MANAGEMENT IN BUSINESS ACTIVITIES: THEORETICAL AND PRACTICAL ASPECTS (European Journal of Interdisciplinary Research and Development, 2025)
In the conditions of a market economy, entrepreneurial activity is always associated with a certain level of risk. This article highlights the main types of risks, their causes and effects, as well as practical methods for managing them. Furthermore, it presents scientifically grounded strategies aimed at assessing risks, reducing their impact, and ensuring the stability of enterprises. The article provides managers and entrepreneurs with practical guidelines on the systematic management of business risks.